PEGylated Mesoporous Silica Nanoparticles (MCM-41): A Promising Carrier for the Targeted Delivery of Fenbendazole into Prostrate Cancer Cells - Maedeh Koohi Moftakhari Esfahani; Seyed Ebrahim Alavi; Peter J. Cabot; Nazrul Islam; Emad L. Izake (Pharmaceutics, 2021)
Low water solubility and thus low bioavailability limit the clinical application of fenbendazole (FBZ) as a potential anticancer drug. Solubilizing agents, such as Mobil Composition of Matter Number 41 (MCM) as a drug carrier, can improve the water solubility of drugs. In this study, PEGylated MCM (PEG-MCM) nanoparticles (NPs) were synthesized and loaded with FBZ (PEG-MCM-FBZ) to improve its solubility and, as a result, its cytotoxicity effect against human prostate cancer PC-3 cells. The loading efficiency of FBZ onto PEG-MCM NPs was 17.2%. The size and zeta potential of PEG-MCM-FBZ NPs were 366.3 ± 6.9 nm and 24.7 ± 0.4 mV, respectively. They had a spherical shape and released the drug in a controlled manner at pH 1.2 and pH 6.2. PEG-MCM-FBZ were found to inhibit the migration of PC-3 cells, increase the cytotoxicity effects of FBZ against PC-3 cells by 3.8-fold, and were more potent by 1.4-fold, when compared to the non-PEGylated NPs. In addition, PEG-MCM-FBZ promoted the production of reactive oxygen species by 1.3- and 1.2-fold, respectively, when compared to FBZ and MCM-FBZ. Overall, the results demonstrate that PEG-MCM-FBZ NPs enhanced FBZ delivery to PC-3 cells; therefore, they have the potential to treat prostate cancer after a comprehensive in vivo study.